2016
DOI: 10.1038/npjamd.2016.8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen stimulates the gene expression of transcriptional coactivator PGC-1α to enhance fatty acid metabolism

Abstract: We previously reported that molecular hydrogen (H2) acts as a novel antioxidant to exhibit multiple functions. Moreover, long-term drinking of H2-water (water infused with H2) enhanced energy expenditure to improve obesity and diabetes in db/db mice accompanied by the increased expression of fibroblast growth factor 21 (FGF21) by an unknown mechanism. H2 was ingested by drinking of H2-water or by oral administration of an H2-producing material, MgH2. The comprehensive gene expression profile in the liver of db… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…Molecular hydrogen was reported to activate PGC-1α (28), which enhances mitochondrial activity (29), thereby rescuing exhausted CD8 + T cells with inactive mitochondria following progressive loss of PGC-1α (15). Therefore, the present study investigated whether hydrogen gas alters the proportion of PD- CD8 + T cell ratio was found to be an independent predictor of poor PFS (HR, 6.459; 95% CI, 2.384-17.50; P<0.0001) and OS (HR, 2.957; 95% CI, 1.185-7.378; P=0.020).…”
Section: Hydrogen Gas Reduces the Proportion Of Pd-1 + Cd8 + T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular hydrogen was reported to activate PGC-1α (28), which enhances mitochondrial activity (29), thereby rescuing exhausted CD8 + T cells with inactive mitochondria following progressive loss of PGC-1α (15). Therefore, the present study investigated whether hydrogen gas alters the proportion of PD- CD8 + T cell ratio was found to be an independent predictor of poor PFS (HR, 6.459; 95% CI, 2.384-17.50; P<0.0001) and OS (HR, 2.957; 95% CI, 1.185-7.378; P=0.020).…”
Section: Hydrogen Gas Reduces the Proportion Of Pd-1 + Cd8 + T Cellsmentioning
confidence: 99%
“…It was recently reported that exhausted CD8 + T cells exhibit mitochondrial dysfunction, caused by the inactivation of PGC-1α, to express immune checkpoint inhibitors such as PD-1 and Tim-3, but return to the active effector state following exposure to certain stimulants (7). Hydrogen was recently reported to stimulate PGC-1α (28), which enhances mitochondrial function (29) and thus may rescue exhausted CD8 + T cells. The present study found that hydrogen gas reduced the proportion of all four PD-1 + CD8 + T cell subsets and increased the proportions of all four PD-1 -CD8 + subsets.…”
Section: Terminalmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Molecular hydrogen modulates signal transduction, protein phosphorylation cascades, gene expression, autophagy, miRNA expression, as well as has important metabolic effects. 5,6 H 2 can induce the Keap1/Nrf2 signaling pathway, 7 promote mitochondrial biogenesis, 8 and the cytoprotective mitochondrial unfolded protein response. 9 H 2 has been proposed to act as an exercise mimetic and redox adaptogen via activating hormetic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The level of total Akt has also been measured in a number of cellular studies and shown remaining unchanged throughout the study (Data not shown). A previous study reported that H 2 suppressed lipid peroxidation, resulting in a decrease in its end-product, 4hydroxy-2noneal (4HNE), and that 4-HNE modified Akt activation [26]. Thus it is possible the H2 indirectly contributes to insulin signaling [25].…”
Section: Impact Of Hydrogenized Water On Cellular Insulin Signaling Amentioning
confidence: 99%